2018
DOI: 10.1111/bcpt.13111
|View full text |Cite
|
Sign up to set email alerts
|

Association between dopamine receptor gene polymorphisms and effects of risperidone treatment: A systematic review and meta‐analysis

Abstract: Our result supported the hypothesis that DRD2 affected risperidone treatment. DRD1 had no significant effect on the response to risperidone, whereas DRD3 might be associated with an improvement in negative symptoms. Larger observational studies are warranted to verify these findings and identify other genetic factors involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
3
12
0
2
Order By: Relevance
“…Recently, consistently with our results, a meta-analysis reported an association between A allele and a significant greater improvement with risperidone treatment. 44 Finally, we did not replicate the association between Taq1A, C939T, and C376G and the AP response in schizophrenia patients.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Recently, consistently with our results, a meta-analysis reported an association between A allele and a significant greater improvement with risperidone treatment. 44 Finally, we did not replicate the association between Taq1A, C939T, and C376G and the AP response in schizophrenia patients.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, Hwang et al 47 found a gene × gene interaction between the Gly allele/ DRD3 and the G allele/ DRD1 in ultraresistant patients with schizophrenia. Ebstein et al, 48 Lane et al, 21 and Ma et al, 44 in three different ethnic groups, established an association between response to conventional APs and the Ser allele. However, other studies have reported an association between the response and the Gly allele.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, when the haplotype block CCGCCGTT (rs6277-rs1076560-rs2283265-rs2734833-rs2075652-rs1079596-rs4436578-rs11214607) was considered, phenotypic associations of the block were found to be associated with heroin dependence behavior [ 26 ]. As a clinically actionable target, a metanalysis has supported the hypothesis that rs6277 potentially alters response to risperidone treatment of schizophrenia [ 31 ], possibly doing so through altered expression, although a definitive conclusion could not be found at this time.…”
Section: Discussionmentioning
confidence: 99%
“…В поле зрения учёных преимущественно попадают рецепторы дофамина 2, 3 и 4-го типов, поскольку в основном они связаны с фармакодинамикой антипсихотиков [3]. Существуют несколько мета-анализов, подтверждающих связь между носительством полиморфизмов гена DRD2 и недостаточным ответом на антипсихотики [8,9]. Полиморфизм DRD3 rs6280 также демонстрировал ассоциацию с исходами лечения антипсихотиками [10,11].…”
Section: введение / Introductionunclassified